La arquitectura política (2019)
Within the desert of urbanized reality, the city has to be founded again, because the disorientation of the traveler demands it. We must establish a center, or several, that orbit around this anonymous mass in order to build islands that can gradually unfold into a civic metastasis, using these terms appropriately without sounding ridiculous. It is from the architecture, and not from the infrastructure, how these new centers have to conform, and it can not be any architecture or any program, but one that rekindles the civic spirit and that gives us a territorial and internal orientation, to return to the path lost to the Truth, to the nature of men. The architectural form can be defined as the experience of a limit, as the relationship between inside and outside. The form exists from the moment in which it represents the tension of the interior with respect to the exterior. Involves an act of spatial determination: delimit.